Storm signals: contemporary essays on mission and discipleship. - Ingleby, Jonathan (Regnum studies in mission., 2016)
Two themes in general run through this book: conflict--both good and bad--and the way our thinking is still configured by empire. We are trapped in imperialistic mindsets, not simply the "old" imperialism of Western colonialism, but managerial globalism with its distaste for the local and contextual and its celebration of business-style organization and "results." We desperately need new ideas and new vision that will carry us beyond these sad relics of modernity, and these essays ask some important questions that will get people talking